2020
DOI: 10.3390/mi11070691
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Probe Integrated Device for Spatiotemporal 3D Chemical Stimulation in Cells

Abstract: Numerous in vitro studies have been conducted in conventional static cell culture systems. However, most of the results represent an average response from a population of cells regardless of their local microenvironment. A microfluidic probe is a non-contact technology that has been widely used to perform local chemical stimulation within a restricted space, providing elaborated modulation and analysis of cellular responses within the microenvironment. Although microfluidic probes developed earlier have variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…We expect that the isolated ST culture method would open a new platform for precision culture experiments, especially when combined with microfluidic technologies. It has been reported that microfluidic systems can produce a continuous microflow of culture medium to produce a desired concentration gradient of a biochemical [ 37 , 38 ]. Combined with such technologies, isolated ST culture experiments could reveal the regulatory mechanisms of spermatogenesis, which have been difficult to elucidate to date.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the isolated ST culture method would open a new platform for precision culture experiments, especially when combined with microfluidic technologies. It has been reported that microfluidic systems can produce a continuous microflow of culture medium to produce a desired concentration gradient of a biochemical [ 37 , 38 ]. Combined with such technologies, isolated ST culture experiments could reveal the regulatory mechanisms of spermatogenesis, which have been difficult to elucidate to date.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of liquid exchange is critical in biomedical and biophysical fields since it enables the switching of the extracellular environment, thereby exposing cells to stimulation and detection simultaneously [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This allows for the direct observation of detailed and dynamic cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is a probe with a pumps system. A probe with a pumps system has shown great promise in controlling fluid flow with a high response speed and high accuracy volume adjustment [ 16 , 17 , 18 , 19 , 20 , 21 , 29 , 30 ]. Recent research has demonstrated that this system was utilized to inject and withdraw solutions in an open space by simultaneously applying positive and negative pressure at adjacent barrels of a probe to form a hydrodynamically confined flow volume at the probe tip [ 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches to create continuous interfaces of the hydrogel to the adjoining fluid in closed channels have emerged, such as the use of phase guides, stepped height channels, recoverable elastic barriers, and alignment of core–shells, but these require multilayer fabrication and assembly. Rail-based capillary-pinning approaches for the patterning of open-top 3D cell cultures have been reported ,, but are static and without the fluidic control needed to deliver chemical gradients for dose/drug response assays or directed migration studies. Microfluidic probes (MFPs) to deliver gradients to open-top cell cultures by using injection and aspiration flows require careful optimization of the geometry and flow rates of the probes. Also, these are impractical for use in patterned 3D hydrogel cultures due to limited depth control of the confined fluid and depletion of the medium that immerses the 3D culture. To address these issues, we present a PDMS-free open microfluidic system (Figure A) integrating the patterned cell-laden hydrogel (∼1 mm depth) with adjoining longitudinal microchannels for dynamic flow control to create chemotactic gradients across the 3D culture width to direct glioma cell migration.…”
mentioning
confidence: 99%
“…Microfluidic probes (MFPs) to deliver gradients to open-top cell cultures by using injection and aspiration flows 30 38 require careful optimization of the geometry and flow rates of the probes. 35 40 Also, these are impractical for use in patterned 3D hydrogel cultures due to limited depth control of the confined fluid and depletion of the medium that immerses the 3D culture. To address these issues, we present a PDMS-free open microfluidic system ( Figure 1 A) integrating the patterned cell-laden hydrogel (∼1 mm depth) with adjoining longitudinal microchannels for dynamic flow control to create chemotactic gradients across the 3D culture width to direct glioma cell migration.…”
mentioning
confidence: 99%